Correction: A new point-of-care test for the diagnosis of infectious diseases based on multiplex lateral flow immunoassays. Issue 17 (8th August 2019) - Kim, Hanbi; Chung, Doo-Ryeon; Kang, Minhee
Abstract : Correction for 'A new point-of-care test for the diagnosis of infectious diseases based on multiplex lateral flow immunoassays' by Hanbi Kim et al., Analyst, 2019, 144, 2460–2466.